Rainforest researchers - Castner, James L. (New York : Benchmark Books/Marshall Cavendish, 2002)
Presents an introduction to six scientists, Jane Goodall, Don Wilson, James Duke, Gary Hartshorn, Terry Erwin, Paul Donahue, and Teresa Wood, who work in the rain forests of South America, and discusses what they have learned from their research.
Includes bibliographical references (p. 61) and index.
School Library Journal, January 2002
Booklist, December 2001
Book Report, March 2002
8.1
5-8
Keywords: Rain forests -- Research; Amazon River Region